2003
DOI: 10.1093/annonc/mdg248
|View full text |Cite
|
Sign up to set email alerts
|

Phase I and pharmacokinetic study of CCI-779, a novel cytostatic cell-cycle inhibitor, in combination with 5-fluorouracil and leucovorin in patients with advanced solid tumors

Abstract: The safety profiles of CCI-779 and 5-FU/LV suggest an overlap of drug-related toxicities, and the administration of these drugs at these doses and schedule resulted in unacceptable toxicity and therefore cannot be recommended. If CCI-779 is to be used in combination with 5-FU/LV, other doses or schedules of administration will need to be explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
2
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(76 citation statements)
references
References 7 publications
2
71
2
1
Order By: Relevance
“…No pharmacokinetic interactions were apparent, and neutropenia was the only toxicity considered dose limiting. It is noteworthy that previous attempts to combine mTOR inhibitors with cytotoxic agents were associated with an increased incidence of toxicity that included dose-limiting diarrhoea and stomatitis with 5-fluorouracil (Punt et al, 2003) and thrombocytopenia with gemcitabine (Pacey et al, 2004). In this regard, the feasibility of combining everolimus with paclitaxel at clinically effective doses of each agent and the delayed tumour progression observed in this heavily pretreated population warrant further investigation in paclitaxelsensitive tumours.…”
Section: Discussionmentioning
confidence: 99%
“…No pharmacokinetic interactions were apparent, and neutropenia was the only toxicity considered dose limiting. It is noteworthy that previous attempts to combine mTOR inhibitors with cytotoxic agents were associated with an increased incidence of toxicity that included dose-limiting diarrhoea and stomatitis with 5-fluorouracil (Punt et al, 2003) and thrombocytopenia with gemcitabine (Pacey et al, 2004). In this regard, the feasibility of combining everolimus with paclitaxel at clinically effective doses of each agent and the delayed tumour progression observed in this heavily pretreated population warrant further investigation in paclitaxelsensitive tumours.…”
Section: Discussionmentioning
confidence: 99%
“…The bioanalytic method for sirolimus was validated through the quantitation range of 0.1 -100 ng ml À1 and exhibited interday and intraday variabilities of o12.7% and biases of o11.3% (Punt et al, 2003). No interferences were observed in blank blood or in blood spiked with internal standard.…”
Section: Bioanalytic Assaysmentioning
confidence: 98%
“…The concentrations of temsirolimus and sirolimus in blood were measured simultaneously using validated liquid chromatography/ tandem mass spectrometry combination procedures with deuterated internal standard (Punt et al, 2003). Analytes and internal standard were extracted from a 1-ml sample of EDTA-treated whole blood by liquid -liquid extraction with 1-chlorobutane and separated with a YMC PDS AQ HPLC column (Waters, Milford, MA, USA).…”
Section: Bioanalytic Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from phase 1 studies evaluating temsirolimus with interferon-alpha, 94 and 5-fluorouracil 95 showed enhanced toxicities at relatively low doses. Similar to the experience with temsirolimus, phase I studies of everolimus combined with gemcitabine 96 and with gefitinib 97 demonstrated limiting toxicities at doses considerably less than the recommended phase II single agent doses.…”
Section: Combination Studies With Sirolimus Derivativesmentioning
confidence: 99%